Analisis Faktor Resiko yang Berhubungan dengan Kejadian Hipertensi pada Kepala Keluarga di Desa Waesala Kabupaten Seram Bagian Barat Provinsi Maluku Tahun 2024 - Iksan Soumena; Asriwati Asriwati; Darwin Syamsul (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Hypertension is a non-communicable disease (ncd) which is a major problem in the health sector and continues to increase every year even though many preventive and promotive measures have been developed following advances in science and technology. to find out analysis of risk factors related to the incident of hypertension in heads of families in tatinang and tita mandiri village waesala regency seram bagin barat tahun 2024. This type of research uses quantitative methods with a cross sectional approach. sampling method used a total sample population of 133 people. data analysis was carried out using univariate, bivariate analysis with chi square and multivariate analysis with logistic regression. Based on the results of the stress logistic regression test, p = 0.042; smoking p = 0.998; alcohol p = 0.996, and diet p = 0.000. diet is the dominant factor with a logistic regression value of p = 0.000 with an or or exp (b) = 12,722. There is a relationship between stress levels, smoking, alcohol and diet. these are the most dominant factors related to the incidence of hypertension in the tatitang and tita mandiri hamlets, while the age factor is not related to the incidence of hypertension.